Impact of pregnancy and risk factors for ventricular arrhythmias in women with tetralogy of Fallot. Issue 1 (7th January 2021) - Quattrone, Alessia; Lie, Oyvind H; Nestaas, Eirik; de Lange, Charlotte; Try, Kirsti; Lindberg, Harald L; Skulstad, Helge; Erikssen, Gunnar; Edvardsen, Thor; Haugaa, Kristina; Estensen, Mette E
Abstract : Objective: Patients with tetralogy of Fallot (TOF) have high survival rates 30 years after surgical repair. Many patients experience pregnancy; however, the effects of pregnancy on the long-term cardiovascular outcome are not well known. We investigated the association of pregnancy and cardiac function with occurrence of ventricular arrhythmia (VA) in women with TOF. Methods: We recruited 80 women with repaired TOF from the national database. Holter monitoring or implanted devices detected VA, defined as non-sustained or sustained ventricular tachycardia or aborted cardiac arrest. All patients underwent echocardiography. Blood tests included NT-proBNP (N-terminal pro-brain natriuretic peptide). Results: 55 (69%) women had experienced pregnancy. Mean age was lower in nulliparous compared with those with children (30±9 vs 40±9, p<0.01). VA had occurred in 17 (21%) women. Prevalence of VA was higher in women who had experienced pregnancy (n=16, 94%) compared with nulliparous (n=1, 6%) (p=0.02), also when adjusted for age (OR 12.9 (95% CI 1.5 to 113.2), p=0.02). Right ventricular mechanical dispersion was more pronounced in patients with VA (50±8 ms vs 39±14 ms, p=0.01, age-adjusted OR 2.1 (95% CI 1.3 to 7.5), p=0.01). NT-proBNP was also a marker of VA (211 ng/L (127 to 836) vs 139 ng/L (30 to 465), p=0.007). NT-proBNP >321 ng/L (normal values <170 ng/L) detected women with VA (p=0.019), also independent of age (OR 7.2 (95% CI 1.7 to 30.1), p=0.007). Conclusion: Pregnancy was associated with higher prevalence of VA among women with TOF. Right ventricular mechanical dispersion and NT-proBNP were age-independent markers of VA. These may have importance for pregnancy counselling and risk stratification.